Transforming higher education delivery in South Africa, lessons and experiences of CIDA City Campus - Okokoh, A. B. C. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (School of Public Management and Planning))--University of Stellenbosch, 2007.